Potensi Ekosistem Terumbu Karang di Taman Wisata Perairan Gili Sulat dan Gili Lawang Lombok Timur - Akhyar, Lalu Ainul; Prasetyo, Budi (MANILKARA: Journal of Bioscience, 2022)
Coral reefs are one of the ecosystems that play an important role in coastal areas but are vulnerable to change. Ecologically, coral reefs act as habitats for various kinds of reef fish, in addition to functioning as beach protectors from the crashing waves of currents as well as a source of germplasm. The diversity of coral genera and other biota is one of the important indicators in supporting the sustainability of water tourism activities, especially snorkeling and diving. Areas that have relatively high diversity of coral reefs have more resilience in their role in protecting coastal areas so that their existence needs to be maintained in order to avoid extinction. This study aims to identify the names of coral genera and measure the percentage of coral cover in the Gili Sulat and Gili Lawang Water Tourism Parks (WTP). The method used in this research is the Point Intercept Transect (PIT) method and the Time Swim method. The results showed that 10 genera had been identified, namely the genus Acropora, Euphyllia, Fungia, Galaxea, Lobophyllia, Montastrea, Montipora, Pachyseris, Plerogyra, and Porites. The largest coral genera were Porites and Acropora which were spread on transects 1 and 7. The average coverage of the two corals was 32.34% in Gili Sulat and 39.64% in Gili Lawang.